The Scanning Fiber Endoscope: A Novel Surgical and High-Resolution Imaging Device for Intracranial Neurosurgery. Issue 4 (10th October 2022) - Walker, Gregory; Wang, Alick P.; McVeigh, Patrick Z.; Ivanishvilli, Zurab; Siu, William; Seibel, Eric J.; Lesiuk, Howard; Alkherayf, Fahad; Drake, Brian J.
Abstract : BACKGROUND: The scanning fiber endoscope (SFE) is a novel medical imaging device that has been used in various vascular beds as a form of angioscopy, as well as in tracts and duct systems for endoluminal imaging. Owing to its miniaturized form, high resolution, and flexibility, it has demonstrated success in imaging across a wide range of diagnostic applications. OBJECTIVE: To demonstrate, by performing a third ventriculostomy and visualizing the cranial nerves and brainstem anatomy, that, without modification, the SFE can be used through a transcranial approach in a therapeutic intraventricular neurosurgical application. METHODS: A 3.7 French SFE system was used without modification on a live porcine model to perform a third ventriculostomy and acquire high-resolution images of the animal's ventricular system, cranial nerves, and brainstem. A side-by-side comparison was made with one of the current standard-of-care rigid endoscopes as a context for size and image quality. RESULTS: High-resolution video-rate imaging was used to assist the successful, uncomplicated performance of a third ventriculostomy. High-resolution endoscopic images of the brainstem and cranial nerves were acquired. CONCLUSION: Although the SFE has been shown to be a superior device for imaging, here we demonstrate its first use as a potential therapeutic device in intracranial neurosurgery.